1970
DOI: 10.1192/bjp.116.531.161
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Psychological Symptoms in Women Taking Oral Contraceptives

Abstract: The premenstrual syndrome first described by Frank (1931) includes a number of psychological and physical symptoms appearing in the week before menstruation and relieved by the onset of the period. The aetiology is still obscure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Depression is among the many reported premenstrual symptoms [46,47]. It has also been suggested that use of oral contraceptives worsens depressive symptoms [13,[48][49][50]. We found that dietary intake of vitamin B 6 was more strongly associated with depressive symptoms in an older cohort than total intake or plasma PLP.…”
Section: Discussionsupporting
confidence: 49%
“…Depression is among the many reported premenstrual symptoms [46,47]. It has also been suggested that use of oral contraceptives worsens depressive symptoms [13,[48][49][50]. We found that dietary intake of vitamin B 6 was more strongly associated with depressive symptoms in an older cohort than total intake or plasma PLP.…”
Section: Discussionsupporting
confidence: 49%
“…One of the recognized adverse reactions to oral contraceptives (OC) is depression (1)(2)(3). The control of mood is thought to be related in some way to the function in the brain of serotonin (4) and/or noradrenaline (5) which are synthesized from the precursor amino acids tryptophan and tyrosine following a carrier-mediated transport into the brain (6.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of safe, effective, and reliable contraception coincided with (and arguably led to) second-wave feminism, enabling women to assume formerly inaccessible roles in education, the arts, and the workforce (see discussion in Traulsen, Haugbølle, and Bissell, 2003). In 2007 in the United Kingdom, 40-54% of women aged 16-34 and 27% of women under the age of 50 reported currently using Recently, researchers have documented negative effects on mood and psychological well-being as a consequence of HC use in women (Bancroft, Sanders, Warner, and Loudon, 1987;Herzberg and Coppen, 1970;Kahn and Halbreich, 2001; Kurshan and Epperson, 2006;Oinonen and Mazmanian, 2002). DeSoto, Geary, Hoard, Sheldon, and Cooper (2003) found that women using HCs exhibited more symptoms of borderline personality disorder (BPD), a disorder characterized by a pervasive pattern of instability in affect regulation, impulse control, interpersonal relationships, and self-image (Lieb, Zanarini, Schmahl, Linehan, and Bohus, 2004), and that women with high pre-existing levels of BPD symptoms became significantly worse after starting HC use (DeSoto et al, 2003).…”
Section: Introductionmentioning
confidence: 99%